I became adult when … Pathways of identity resolution and adulthood transition in Italian freshmen's narratives. Issue 3 (3rd July 2018) - Sica, Luigia Simona; Aleni Sestito, Laura; Syed, Moin; McLean, Kate
ABSTRACT: Defining and consolidating identity in order to acquire fulfilling adult roles may be more difficult than in the past for a significant proportion of youth cohorts, especially for youth in 'post-industrial' countries. This study was focused on the intersection between processes and contents of both identity and adulthood through the narrative approach in the Italian context. Participants were 105 Italian freshmen aged 18–21, attending the first year university. We adopted a narrative approach based on autobiographical memories. Findings confirm the relationship between identity resolution processes and adulthood reaching in Italian freshmen and they identify five student's profiles (Resolved or closed keepers, Travelers, Uninvolved, On the way, Big babies). Suggestions for future research and limitations are discussed.